'Selfie'-objectification: The role of selfies in self-objectification and disordered eating in young women. (February 2018) - Cohen, Rachel; Newton-John, Toby; Slater, Amy
Abstract: Existing research demonstrates a relationship between social networking site (SNS) use and body-related concerns and disordered eating amongst females. Preliminary evidence indicates that SNS photo activities (e.g., taking and sharing 'selfies') may play a particularly important role. The present study aimed to use self-objectification as a framework to examine the relationship between SNS photo activities and body-related and eating concerns in a population of young women. Participants were 259 young women (age 18–29; M = 22.97, SD = 3.25) who completed self-report questionnaires of SNS use and body-related and disordered eating concerns. Results showed that SNS 'selfie' activities, rather than general SNS usage, were associated with body-related and eating concerns. Specifically, greater investment in 'selfie' activities was associated with increased body dissatisfaction and bulimia symptomatology, even after accounting for known risk factors such as thin-ideal internalisation and body mass index (BMI). Moreover, self-objectification was found to moderate the relationship between photo investment and bulimia symptomatology. These findings indicate that active engagement with SNS photo activities, rather than general SNS use, shows an association with body-related and eating concerns. Interventions targeting specific SNS photo activities may be an effective avenue for the prevention and management of body-related concerns and disordered eating in young women. Highlights: Overall Social Networking Site (SNS) use is not related to body image in young women. SNS 'selfie' activities are associated with body-related and eating concerns. Self-objectification moderates relationship between selfie activity and disordered eating.